2022
DOI: 10.1101/2022.05.31.494192
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The mIAA7 degron improves auxin-mediated degradation in C. elegans

Abstract: Auxin-inducible degradation (AID) is a powerful tool for the targeted degradation of proteins with spatiotemporal control. One limitation of the AID system is that not all proteins are degraded efficiently. Here, we demonstrate that an alternative degron sequence, termed mIAA7, improves the efficiency of degradation in C. elegans, as previously reported in human cells. We tested depletion of a series of proteins with various sub-cellular localizations in different tissue types and found that the use of the mIA… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 79 publications
1
3
0
Order By: Relevance
“…Although mIAA7-dependent depletion of FOS-1A did not completely recapitulate the null allele phenotype, it significantly improved both the degradation kinetics and associated invasion defects following loss of a transcription factor with single cell specificity. This is in support of the first report using the mIAA7 degron in C. elegans, which emphasized that nuclear localized targets are more resistant to auxin-induced degradation (Sepers et al 2022). To further explore how protein abundance and subcellular localization of a target protein may affect degradation kinetics at singlecell resolution in a functional assay, we generated two new strains to compare the mIAA7 and AID degron kinetics following depletion of arx-2, the sole Arp2 subunit of the actin-related protein-2/3 (Arp2/3) complex in C. elegans (Sawa et al 2003).…”
Section: Ac Specific Degradation Of Abundant Structural Proteins Is M...supporting
confidence: 88%
See 1 more Smart Citation
“…Although mIAA7-dependent depletion of FOS-1A did not completely recapitulate the null allele phenotype, it significantly improved both the degradation kinetics and associated invasion defects following loss of a transcription factor with single cell specificity. This is in support of the first report using the mIAA7 degron in C. elegans, which emphasized that nuclear localized targets are more resistant to auxin-induced degradation (Sepers et al 2022). To further explore how protein abundance and subcellular localization of a target protein may affect degradation kinetics at singlecell resolution in a functional assay, we generated two new strains to compare the mIAA7 and AID degron kinetics following depletion of arx-2, the sole Arp2 subunit of the actin-related protein-2/3 (Arp2/3) complex in C. elegans (Sawa et al 2003).…”
Section: Ac Specific Degradation Of Abundant Structural Proteins Is M...supporting
confidence: 88%
“…The copyright holder for this preprint this version posted October 16, 2022. ; https://doi.org/10.1101/2022.10.14.512315 doi: bioRxiv preprint A recent report in C. elegans demonstrated that an alternative degron sequence, the mIAA7 degron, displayed faster degradation kinetics when paired with At TIR1 expression and auxin treatment (Sepers et al 2022). Compared to the minimal AID epitope, the mIAA7 sequence contains the 44aa domain required for At TIR1 recognition and additional N-terminal flanking sequences from the IAA protein that improve the interactions with TIR1 (Gray et al 2001;Ramos et al 2001) (Fig.…”
Section: The Efficacy Of Ac-specific Degradation Of Fos-1a Is Improve...mentioning
confidence: 99%
“…The auxin-inducible degron (AID) system enables rapid degradation of C. elegans proteins (Ashley et al, 2021; Hills-Muckey et al, 2021; Martinez et al, 2020; Negishi et al, 2021; Sepers et al, 2022; Zhang et al, 2015). It requires a minimal AID tag on the protein of interest (POI), expression of the Arabidopsis F-box protein TIR1, and exogenous exposure to the plant hormone auxin.…”
Section: Resultsmentioning
confidence: 99%
“…2B,F). These ambiguities could be addressed in future studies by creating and/or combining conditional null alleles using the auxin-inducible degron (AID) system (Ashley et al, 2021;Hills-Muckey et al, 2021;Martinez et al, 2020;Negishi et al, 2021;Sepers et al, 2022;Xiao et al, 2023; or an analogous approach (Nance and Frøkjaer-Jensen, 2019).…”
Section: Discussionmentioning
confidence: 99%